CLAROS - bringing classical art to a global public - Kurtz, D; Parker, G; Shotton, D; Klyne, G; Schroff, F; Zisserman, A; Wilks, Y (IEEE, 2010)
CLAROS (Classical Art Research Online Services; www.clarosweb.org) is an international interdisciplinary research initiative led by the University of Oxford (Humanities and Mathematics and Physical Sciences), hosted by the Oxford e-Research Centre (OeRC, www.oerc.ox.ac.uk), and inspired by the Beazley Archive (www.beazley.ox.ac.uk) participating in EU R&D projects. During 2009, a pump-priming grant from the University's Fell Fund enabled CLAROS to integrate on line more than two million records and images held in research centres in Oxford, Paris, Cologne and Berlin. CLAROS uses CIDOC CRM (http://cidoc.ics.forth.gr/), developed under UNESCO's ICOM (http://icom.museum/), to map across datasets and a portfolio of Open Source software to deliver them swiftly to a broad range of global users. Data web applications for integration are being developed by Zoology (http://ibrg.zoo.ox.ac.uk/), image recognition by Engineering Science (www.robots.ox.ac.uk/~vgg/), and artificial intelligence by the Oxford Internet Institute (www.oii.ox.ac.uk). CLAROS will welcome new institutional members and engage with the public to document art and disseminate results.